1999
DOI: 10.1176/ajp.156.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Risk Factors for Alzheimer’s Disease: Results at 7.5 Years

Abstract: These results indicate that increased platelet membrane fluidity is not produced by the APOE epsilon4 allele. Instead, increased platelet membrane fluidity and the epsilon4 allele appear to make significant independent contributions to the risk of developing Alzheimer's disease among the first-degree relatives of patients with this disorder. Moreover, the age ranges over which these risk factors operate appear to be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 81 publications
0
5
0
1
Order By: Relevance
“…Previous studies during the 1980s and 90s reported a possible relationship between increased platelet membrane fluidity, which increases when membrane cholesterol level is reduced, and AD (reviewed by Swiderek et al 1997), although few developments have been published more recently. Internal membranes have a lower ratio of cholesterol to phospholipid than plasma membranes, and the increased platelet membrane fluidity in AD was attributed to a proliferation in internal membranes, rather than changes in plasma membrane lipid composition (Cohen et al 1987;Piletz et al 1991;Zubenko et al 1999). One study also reported a slight (5%) decrease in platelet membrane cholesterol level in a small group (n = 10) of Alzheimer's patients, but this was not statistically significant (Cohen et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies during the 1980s and 90s reported a possible relationship between increased platelet membrane fluidity, which increases when membrane cholesterol level is reduced, and AD (reviewed by Swiderek et al 1997), although few developments have been published more recently. Internal membranes have a lower ratio of cholesterol to phospholipid than plasma membranes, and the increased platelet membrane fluidity in AD was attributed to a proliferation in internal membranes, rather than changes in plasma membrane lipid composition (Cohen et al 1987;Piletz et al 1991;Zubenko et al 1999). One study also reported a slight (5%) decrease in platelet membrane cholesterol level in a small group (n = 10) of Alzheimer's patients, but this was not statistically significant (Cohen et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are frequently used as peripheral markers for neurons because they share some common membrane and receptor properties, providing, thus, an interesting model for the investigation of metabolic abnormalities in AD (Zubenko et al 1999). There is indirect evidence that brain and platelet PLA 2 activity are under similar regulatory control.…”
Section: Cognitive Training Induces Pla 2 Activation In Platelets Of mentioning
confidence: 99%
“…As we are currently unable to have brain or CSF samples from these T2DM patients, we are unfortunately not able to identify whether the platelet GSK-3β activation reflects GSK-3β activation in the central nervous system or to provide direct evidence revealing the possible biological relationship between platelet GSK-3β and cognitive impairment. Nonetheless, platelets are frequently used to search for peripheral biomarkers for the nervous system because they share many biochemical similarities, such as accumulation and release of neurotransmitters, responses to variations of calcium concentration, and expression of receptors and enzymes, and therefore, the platelet has served as an important model for the investigation of metabolic abnormalities in AD ( Zubenko et al, 1999 ; Gattaz et al, 2004 ; Forlenza et al, 2011 ). How exactly the platelet GSK-3β activation may reflect brain GSK-3β activation and its biological relations with cognitive impairment deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%